Geiger-Muller 계수관을 이용한 베타선측정에서 디텍터 보호유무에 따른 계수율 분석 - 장지용; Ji-yong Jang; 정문택; Moon-taeg Jeong; 송종남; Jong-nam Song; 하재준; Jae-jun Ha; 한재복; Jae-bok Han (한국방사선학회 논문지, 2018)
단창형의 Geiger-Muller 계수관을 이용한 표면오염검사에서 베타선을 측정하기 위해 외부로 노출된 디텍터를 보호하는 방법으로 랩을 사용하고 있는데 이 방법이 측정계수율과 교정인자에 미치는 영향을 분석하고 방사선작업종사자에게 과도한 랩의 사용은 베타선의 측정값에 영향을 줄 수 있음을 인지시켜주고자 하였다. 실험방법은 3 KBq, 1.5 KBq, 0.3 KBq의 에너지가 다른 베타선을 이용하여 랩 두께에 따른 베타선 측정계수율과 교정인자의 변화를 비교ㆍ분석하였다. 실험 대상으로는 2012년 3월 한국인정기구 (KOLAS) 인증을 받은 교정센터에서 보유한 단창형의 Geiger-Muller 계수관을 대상으로 하였으며, Cl-36(Chlorine)과 Sr-90(Strontium)을 베타선 방사선원으로 사용하였다. 측정계수율은 랩 두께가 증가할수록 감소함을 확인 할 수 있었고 교정인자는 랩 두께가 증가할수록 증가하는 것을 알 수 있었다. 측정계수율의 감소와 교정인자의 변화는 기기지시값의 정확도를 감소시킬 수 있지만 디텍터의 오염 및 손상 또한 베타선 측정에서 중요한 영향을 주기 때문에 어느 정도 두께의 랩을 사용함이 가장 효과적인지 알아볼 필요성이 있다. 측정계수율과 교정인자의 낮은 변화율을 보여주는 두께의 랩을 사용한다면 디텍터를 보호하면서 베타선의 측정값에도 영향을 최소한으로 줄 수 있을 것으로 사료된다. In the surface contamination test using the end-window Geiger-Muller type counter, the wrap is used as a method for protecting the detector exposed to the outside in order to measure the beta-rays. We analyze the effect of this method on the measurement rate and the correction factor, and wanted to make it clear to radiation workers that excessive use of the wrap can affect the measured value of the beta-rays. The experimental method was to compare and analyze the change of the beta-rays measurement counting rate and the calibration factor according to the wrap thickness using the beta-rays with different energy of 3 KBq, 1.5 KBq and 0.3 KBq. The subjects of this study were the end-window Geiger-Muller type counter which were held at the calibration center certified by Korea Laboratory Accreditation Scheme (KOLAS) in March 2012, Cl-36 (Chlorine) and Sr-90 (Strontium) were used as the source of beta radiation. The measurement counting rate decreased with increasing wrap thickness, and the calibration factor increased with increasing wrap thickness. Since the changes of the measurement counting rate and the calibration factors can reduce the accuracy of the instrument readings, but also have a significant impact on detector contamination and damage, so there is a need to find out what thickness of wrap is most effective. If we using a wraps with thickness that show a low rate of change of the measurement counting rate and the calibration factor, it will protect the detector and minimize the effect on the measured value of the beta-rays.